2012
DOI: 10.5194/acp-12-1021-2012
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene in poplar emissions: effects on new particle formation and OH concentrations

Abstract: Abstract. Stress-induced volatile organic compound (VOC) emissions from transgenic Grey poplar modified in isoprene emission potential were used for the investigation of photochemical secondary organic aerosol (SOA) formation. In poplar, acute ozone stress induces the emission of a wide array of VOCs dominated by sesquiterpenes and aromatic VOCs. Constitutive light-dependent emission of isoprene ranged between 66 nmol m −2 s −1 in non-transgenic controls (wild type WT) and nearly zero (<0.5 nmol m −2 s −1 ) in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 48 publications
2
36
0
Order By: Relevance
“…We derive incremental mass yields of 20 ± 3 % for MeSa and of 17 ± 1 % for SQT from Experiments #1c and #2, respectively (Table 4). The SQT and MeSa incremental yields are about the same within the errors and we conclude that SQT and MeSa must have contributed according to their turnover to the BSOA yields of ≈ 20 % in Experiment #1 (Table 4 and Kiendler-Scharr et al, 2012). Compared to the incremental yields of MT-SOAs, the yields of SQT-SOAs and MeSa-SOAs are about a factor of 4 larger.…”
Section: Bsoa Formation From Constitutive Bvoc Emissions and Siesmentioning
confidence: 80%
“…We derive incremental mass yields of 20 ± 3 % for MeSa and of 17 ± 1 % for SQT from Experiments #1c and #2, respectively (Table 4). The SQT and MeSa incremental yields are about the same within the errors and we conclude that SQT and MeSa must have contributed according to their turnover to the BSOA yields of ≈ 20 % in Experiment #1 (Table 4 and Kiendler-Scharr et al, 2012). Compared to the incremental yields of MT-SOAs, the yields of SQT-SOAs and MeSa-SOAs are about a factor of 4 larger.…”
Section: Bsoa Formation From Constitutive Bvoc Emissions and Siesmentioning
confidence: 80%
“…We examined the sensitivity of the formation of newSOA to the inclusion of the suppression by isoprene in EX2 as described in section based on field measurements that indicated that NPF rarely takes place when the concentration of isoprene is high (Kiendler‐Scharr et al, ; Lee et al, ). The assumption of isoprene suppression in the model causes organic nucleation to shut off in many places, so that the annual global average organic nucleation rate is decreased by 67% (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The second sensitivity case (EX2) was designed to examine the uncertainty of organic nucleation under an isoprene‐rich environment. Some field measurements indicated that isoprene suppresses organic nucleation (Kiendler‐Scharr et al, ; Kiendler‐Scharr et al, ; Lee et al, ). It is clear that NPF rarely takes place when emissions of isoprene are high, although the chemical and physical mechanism of suppression is not clear.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the important impacts of BVOCs on climate, little is known about how individual BVOC species emitted from trees is involved in NPF processes. In particular, isoprene, which accounts for nearly half of the total global BVOC budget [ Guenther et al ., ], is controversial regarding whether this dominant biogenic compound either promotes or suppresses NPF [ Kiendler‐Scharr et al ., ; W. Xu et al ., ]. Additionally, the previous chemical mechanism proposed to explain isoprene's suppression of biogenic NPF contradicts atmospheric observations, as outlined below.…”
Section: Introductionmentioning
confidence: 99%